Continous Renal Replacement Therapy pada Pasien Sepsis, Respiratory Failure, Acute Kidney Injury, dan Asidosis Metabolik - Septian, Dendi; Oktaliansah, Ezra (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2023)
Sepsis is a life-threatening organ dysfunction resulting from dysregulation of the body's response to infection. The hypermetabolic response results in an imbalance between oxygen supply to tissues while oxygen demand in peripheral organs increases. Acute Kidney Injury (AKI) is one of the most common and severe complications of sepsis, and is associated with high mortality and poor outcomes. If pharmacological therapy has been given but there is no clinical improvement, Continuous Renal Replacement Therapy (CRRT) with Continuous Venovenous Hemodiafiltration (CVVHDF) modality can be considered. A 31-year-old male patient came with complaints of shortness of breath, the patient was diagnosed with septic shock accompanied by acute kidney injury and chronic kidney disease. The patient's condition worsened with unstable hemodynamics. CRRT is performed as an option for AKI management in critically ill patients with unstable hemodynamics. There was improvement in renal function, acidosis, and hemodynamics in patients. Renal Replacement Therapy (RRT) is an option for treating AKI in critically ill patients with unstable hemodynamics. CRRT plays an important role in treating septic shock patients with AKI in the intensive care unit.